CaWRKY58, encoding a group I WRKY transcription factor of Capsicum annuum, negatively regulates resistance to Ralstonia solanacearum infection. (11th October 2012) - Wang, Yuna; Dang, Fengfeng; Liu, Zhiqin; Wang, Xu; Eulgem, Thomas; Lai, Yan; Yu, Lu; She, Jianju; Shi, Youliang; Lin, Jinhui; Chen, Chengcong; Guan, Deyi; et al.
Summary WRKY transcription factors are encoded by large gene families across the plant kingdom. So far, their biological and molecular functions in nonmodel plants, including pepper (Capsicum annuum) and other Solanaceae, remain poorly understood. Here, we report on the functional characterization of a new group I WRKY protein from pepper, termed CaWRKY58. Our data indicate that CaWRKY58 can be localized to the nucleus and can activate the transcription of the reporter β‐glucuronidase (GUS) gene driven by the 35S core promoter with two copies of the W‐box in its proximal upstream region. In pepper plants infected with the bacterial pathogen Ralstonia solanacearum, CaWRKY58 transcript levels showed a biphasic response, manifested in an early/transient down‐regulation and late up‐regulation. CaWRKY58 transcripts were suppressed by treatment with methyl jasmonate and abscisic acid. Tobacco plants overexpressing CaWRKY58 did not show any obvious morphological phenotypes, but exhibited disease symptoms of greater severity than did wild‐type plants. The enhanced susceptibility of CaWRKY58‐overexpressing tobacco plants correlated with the decreased expression of hypersensitive response marker genes, as well as various defence‐associated genes. Consistently, CaWRKY58 pepper plants silenced by virus‐induced gene silencing (VIGS) displayed enhanced resistance to the highly virulent R. solanacearum strain FJC100301, and this was correlated with enhanced transcripts of defence‐related pepper genes. Our results suggest that CaWRKY58 acts as a transcriptional activator of negative regulators in the resistance of pepper to R. solanacearum infection.